PENINGKATAN KEMAMPUAN BAHASA PRANCIS LISAN MAHASISWA PRODI BAHASA DAN SASTRA PRANCIS MELALUI TUGAS PEMBUATAN VIDEO VISITE GUIDÉE - Ria Yuliati; Charlotte Simonutti (Universitas Andalas, 2017)
MEA (ASEAN Economics Society) is defined as an agreement among ASEAN leaders in the last decade to make integrated ASEAN economy, namely free trade: goods, services, investation and workers. One important thing to get ready for MEA is foreign language proficiency including French. However, spoken French proficiency of university students is still low. That is why this research intends to solve this problem: what is the strategy to improvestudents speaking ability on French and how to make video visite guidée (tourisme guide using French). This research was Classroom Action Research (CAR) as an action conducted in the class to solve a problem. It used Kurt Lewin cycle: planning, acting, observing, reflecting. The result of the research: an effort to improve students speaking ability on French is by developing a video visite guidée using French. The result of the research has given significances cognitively (knowledge on French), affectively (interest and confidence using French) and psychomotoric (video development). There are some steps to develop video visite guidée.